Pengaruh Penerapan Prinsip Syariah terhadap Tingkat Kepatuhan Pajak di Kalangan UMKM Indonesia - Marshelynda, Alfia Rahmadhanti; Nisa, Fauzatul Laily (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are vital to the nation's economy. However, tax compliance remains a challenge. Interestingly, some believe that the application of Islamic principles (sharia) in financial management can improve MSME tax compliance. This study investigates the potential impact of sharia principles on MSME tax compliance in Indonesia. This research utilizes a quantitative descriptive approach that aims to show a correlation between sharia practices and higher tax compliance among MSMEs. The potential reasons for the correlation are due to strict sharia supervision with sharia compliance ensuring ethical and transparent business practices potentially resulting in more accurate tax reporting, open and fair transactions, sharia principles often encourage responsible business practices that contribute positively to the local economy potentially increasing the sense of civic responsibility and tax compliance. This research also explores the concept of tax from an Islamic economic perspective. Here, taxes are seen as a way to contribute to the welfare of society, in line with the Islamic principle of providing benefits to society. This research highlights the importance of ethical business practices and their potential impact on fulfilling civic obligations such as tax payments.